Hubungan Sekolah Dan Masyarakat Di SMP Negeri 11 Kabupaten Rejang Lebong (Studi Kasus) - Sumiati (UNIVERSITAS BENGKULU, 2024)
This study aims to describe the implementation of school and community relations in SMP Negeri 11 Rejang Lebong. This research is a case study research. The research was conducted at SMP Negeri 11 Rejang Lebong Regency. Research data obtained from interviews, observations and documentation. Research data analysis includes data reduction, data presentation, verification and conclusion drawing. The results showed that the implementation of school and community relations at SMP Negeri 11 Rejang Lebong had been implemented. The school-community relationship development model, which is a one-way asymmetrical model, has internal and external activities.